ANTIPROLIFERATIVE AND IN SILICO ADMET STUDY OF NEW 4-(PIPERIDIN-1-YLMETHYL)-2- (THIOPHEN-2-YL) QUINOLINE ANALOGUES - S, Harishkumar; Nd, Satyanarayan; Sm, Santhosha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Synthesis and antiproliferative study of novel 4-(piperidin-1-ylmethyl)-2-(thiophen-2-yl) quinoline 7(a-j) derivatives. Methods: 4-(piperidin-1-ylmethyl)-2-(thiophen-2-yl) quinolines were synthesized by the addition of 4-(chloromethyl)-2-(thiophen-2-yl) quinoline (0.01 mol), piperidine (0.01 mol) in DMF (10 v) and K2CO3 (0.02 mol). The anticancer activity of the title compounds performed against T-47D, HeLa, HepG2, and MCF-7 human cancer cell lines growth was investigated by MTT assay. Results: The compounds 7b and 7g exhibited 90% of the growth inhibitory effect on T-47D, HeLa, and MCF-7 and also 80% growth inhibition in HepG2 when compared with standard drug paclitaxel. Conclusion: The synthesized compounds 4-(piperidin-1-ylmethyl)-2-(thiophen-2-yl) quinoline 7(a-j) exhibited a considerable degree of growth inhibition of human cancer cell lines. The synthesized molecules 7(a-j) are in acceptable range and are less toxic and can be considered as possible hits for drug discovery.